All tangled up: interactions of the fibrinolytic and innate immune systems - Whyte, Claire S. (Frontiers in Medicine, 2023)
The hemostatic and innate immune system are intertwined processes. Inflammation within the vasculature promotes thrombus development, whilst fibrin forms part of the innate immune response to trap invading pathogens. The awareness of these interlinked process has resulted in the coining of the terms “thromboinflammation” and “immunothrombosis.” Once a thrombus is formed it is up to the fibrinolytic system to resolve these clots and remove them from the vasculature. Immune cells contain an arsenal of fibrinolytic regulators and plasmin, the central fibrinolytic enzyme. The fibrinolytic proteins in turn have diverse roles in immunoregulation. Here, the intricate relationship between the fibrinolytic and innate immune system will be discussed.